Pengembangan Media Pembelajaran Interaktif Berbasis Video Animasi Untuk Meningkatkan Minat Belajar Siswa SD - H, Maryam (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
the field, students’ interest in learning is still very low. The purpose of this research is to develop interactive learning media based on video animation in attracting learning learning interest of elementary school students in Pohuwato Regency. The research method used is the Dick & Carry research method with the aim of making video-based interactive learning for all elementary school students in Pohuwato Regency and determining the quality of interactive media based on assessment of media experts have an average feasibility value of 95 in the good category, while material experts have an average feasibility 97,53%, in the very good category. Small group trials have an average score of 83.94 %, in the good category. The results of the teachers assessment obtained an average score of 97, % in the very good category.